The Impact of Physical Exercise on Prosocial Behaviour among College Students on Pro-Social Behaviour - Ting Luo; Haoliang Mai; Shuo Yu; Haiqing Wang; Weilin Su, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study explores the effects of physical exercise on the prosocial behaviour of college students, based on questionnaires. Online and offline methods were employed to collect 952 valid questionnaires, given the high response rate of 98.70% and effective rate of 96.45%. The research explores the mediating roles of body self-esteem and peer relationships in the exercise-prosocial behaviour link, alongside assessing the moderating influence of Body Mass Index (BMI) on the relationship between physical exercise and body self-esteem. Data were gathered using the Prosocial Behaviour Tendency Scale, Peer Relationship Scale, Body Self-Esteem Scale, Physical Activity Level Scale, and General Information Survey, and were analysed using SPSS 27.0 and the PROCESS plugin to conduct descriptive statistics, independent samples t-tests, correlation analysis, regression analysis, and mediation tests. Findings indicated no significant gender differences in physical exercise, body self-esteem, peer relationships, and prosocial behaviour (ps > 0.05), but significant differences based on registered residence and whether participants were only children (ps < 0.001). Significant correlations emerged among physical exercise, body self-esteem, peer relationships, prosocial behaviour, and BMI (ps < 0.001). In a multiple mediation model, physical exercise did not directly predict prosocial behaviour (β = -0.016, p > 0.05), but exerted an indirect effect through peer relationships (p < 0.001) and body self-esteem (p < 0.001), supporting the parallel multiple mediation model. Additionally, BMI moderated the relationship between physical exercise and body self-esteem (β = 0.223, p < 0.001). The study emphasizes that promoting physical exercise among college students can enhance body self-esteem, peer relationships, and prosocial behaviour, contributing positively to their physical and psychological well-being and fostering a harmonious campus environment. Universities are encouraged to facilitate physical activity through organized sports, competitions, and recreational pursuits such as hiking and cycling, while ensuring safety measures to protect students' physical and mental health.